Еarly Pregnancy Diagnosis in Bulgarian Murrah Buffaloes by Measurement of Pregnancy-Associated Glycoproteins (PAGs) in Blood Serum and Milk - Fasulkov, Ivan; Ilieva, Yordanka; Penchev, Pencho; Karadaev, Мanol; Ivanova, Boyаna; Nenova , Radena; Vasilev, Nasko (Acta Scientiae Veterinariae, 2025)
Background: The timely and accurate pregnancy diagnosis in productive animals allows improving reproductive performance by reduction of the calving interval. The tests for assay of maternal blood pregnancy-associated glycoproteins (PAGs) have been developed for pregnancy diagnosis in large ruminants. The present study aimed to evaluate the efficacy of commercial ELISA kits for detection of pregnancy-associated glycoproteins (PAGs) in blood serum and milk for early pregnancy diagnosis in Bulgarian Murrah buffaloes. Materials, Methods & Results: Blood samples were collected from 57 buffaloes and 27 heifers along with 55 milk samples on the 28th day following artificial insemination. The pregnancy was confirmed on the 35th day by transrectal ultrasonography. Blood serum and milk PAGs concentrations were assayed with commercial PAGs ELISA kit for early pregnancy diagnosis. The data were analyzed by a non-parametric Chi-square test for comparison of proportions with Statistica 7 (StatSoft, Microsoft Corp. 1984-2000 Inc.) statistical software. Serum PAGs values were statistically significantly higher than those in milk (P < 0.05). Based on the collected samples, S-N values for serum PAGs 28 days following artificial insemination of buffaloes, 17 animals were classified as pregnant and 40 – as non-pregnant. In heifers, 7 positive diagnosis of early pregnancy vs 20 negative diagnoses were obtained. The assay parameters - sensitivity, specificity and accuracy - were within acceptable ranges for both tests, with superior results for serum PAGs than for milk PAGs test. The tests had a high sensitivity and accuracy for early diagnosis of pregnancy in buffaloes and heifers on the 28th day after artificial insemination. The sensitivity of the test in the present study was acceptable, 94.4% for the serum and 87.5% for the milk PAGs ELISA in buffaloes, but low in heifers (55.6%). In terms of specificity, absolute values of PAGs tests in serum and milk were recorded in buffaloes and 88.9% for the serum ELISA in heifers. The accuracy of the serum and milk ELISA tests on the 28th day after artificial insemination was 98.2% and 96.4% respectively for buffaloes and 77.8% for the serum test in heifers. The rates of positively predicted diagnoses (PPV) for the serum and milk PAGs tests were 100% in buffaloes and 71.4% in heifers. The negative predicted values (NPV) were 95.1% and 100% respectively in buffaloes and 80.0% in heifers. Discussion: The PAGs ELISA developed in the last years is a very useful tool in early pregnancy diagnosis, especially in large ruminants raised for milk. However, collection of blood causes stress to the animals. Thus, the use of milk as an alternative for performing pregnancy tests in buffaloes has attracted increasing interest from buffalo farmers The present study highlights the advantage of using a milk sample rather than blood for PAGs assay as a non-invasive technique causing minimum stress to the potentially pregnant animals. More importantly, the presence of PAGs in milk provides the possibility to identify pregnant buffaloes within a relatively early period following insemination, allowing for timely inclusion of non-pregnant animals in breeding programs. The analysis of the sensitivity, specificity and accuracy of obtained results from PAGs in serum and milk, as well as the positive and negative diagnoses made showed that they were within acceptable limits. Based on the results obtained for PAGs in serum and milk it may be assumed that PAG ELISA tests are sufficiently specific, sensitive and accuracy for early pregnancy diagnosis on the 28th day after artificial insemination at buffalo farms. Keywords: pregnancy-associated glycoproteins, serum and milk, ruminants, buffaloеs, ELISA.